Coriolopsis rigida, a potential model of white‑rot fungi that produce extracellular laccases - Saparrat, Mario (2014)
In the last two decades, a significant amount of work aimed at studying the ability of the white-rot fungus Coriolopsis rigida strain LPSC no. 232 to degrade lignin, sterols, as well as several hazardous pollutants like dyes and aliphatic and aromatic fractions of crude oil, including polycyclic aromatic hydrocarbons, has been performed. Additionally, C. rigida in association with arbuscular mycorrhizal fungi appears to enhance plant growth, albeit the physiological and molecular bases of this effect remain to be elucidated. C. rigida's ability to degrade lignin and lignin-related compounds and the capacity to transform the aromatic fraction of crude oil in the soil might be partially ascribed to its ligninolytic enzyme system. Two extracellular laccases are the only enzymatic components of its lignin-degrading system. We reviewed the most relevant findings regarding the activity and role of C. rigida LPSC no. 232 and its laccases and discussed the work that remains to be done in order to assess, more precisely, the potential use of this fungus and its extracellular enzymes as a model in several applied processes.